Analysis of Determinants for the Optimization of Restaurant Tax Revenue in North Sumatra Province (Study on Regencies/cities in North Sumatra from 2018 to 2022) - Mei Linda Suryanti Lubis; Asmuni Asmuni; Nurlaila Nurlaila; Murdifin azhar (Faculty of Law, Universitas Pekalongan, 2024)
According to Law No. 28 of 2009, taxes are contributions from the community used for national purposes to ensure the prosperity of the people. This law also explains the existence of Regional Taxes and Levies (PDRD such as the Restaurant Tax. Each year, the Regional Tax and Levy Management Agency sets targets, but many of these targets are not achieve. For example, in 2020 and 2021, many tapping box devices were installed to optimize tax collection, but the targets were still not achieved. Therefore, the purpose of this study is to assess other factors that can optimize tax revenue through the analysis of determinants for the optimization of restaurant tax revenue in North Sumatra Province. This research will take samples from five cities and regencies in North Sumatra Province: Medan, Deli Serdang, Tebing Tinggi, Batu Bara, and Serdang Bedagai. The study will use a quantitative method with primary data collected through surveys. The results of this research indicate that tax audits, tapping box applications, and tax regulations significantly influence taxpayer compliance in paying restaurant taxes in North Sumatra Province. Additionally, tax audits and tapping box applications have a substantial impact on tax optimization, whereas tax regulations do not have a significant impact on the optimization of restaurant taxes in North Sumatra Province. Furthermore, taxpayer compliance does not significantly affect the optimization of restaurant taxes in North Sumatra Province. Finally, tax audits, tapping box applications, and tax regulations do not significantly influence the optimization of restaurant taxes through taxpayer compliance in paying restaurant taxes in North Sumatra Province.